2017
DOI: 10.1007/s00170-017-1396-5
|View full text |Cite
|
Sign up to set email alerts
|

Plunge cylindrical grinding with the minimum quantity lubrication coolant technique assisted with wheel cleaning system

Abstract: MQL technique is considered as a cleaner machining compared to the conventional coolant delivery one, thereby ensuring environmental sustainability and economic benefits. However, one of problems commonly reported when using the MQL technique is the wheel clogging phenomenon as a result of the inefficient chip removal from the cutting zone, then the chips lodge inside the pores of the grinding wheel, adversely affecting the quality and the finishing of the final product. In this context, this study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 30 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The air-oil aerosol covers the GWAS and the workpiece surface, cooling down and applying a lubricating film of oil on the workpiece surface. This allows to reduce the friction force between the abrasive grains and the workpiece surface as well as to reduce the grinding force F c and the amount of heat generated [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…The air-oil aerosol covers the GWAS and the workpiece surface, cooling down and applying a lubricating film of oil on the workpiece surface. This allows to reduce the friction force between the abrasive grains and the workpiece surface as well as to reduce the grinding force F c and the amount of heat generated [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Minimum Quantity Lubrication (Mql)mentioning
confidence: 99%
“…At the same time, these works took into account the possibility of minimising the amount of coolants delivered. In this context, the most frequent description in the literature is the minimum quantity lubrication (MQL) method, the possibilities of which have been analysed in relation to machining [15,16] as well as with respect to the grinding process in general [17][18][19][20][21][22][23][24][25][26][27][28]. Most often, researchers focus on surface grinding process [29][30][31][32], but the possibilities of the MQL method in the grinding of hard-to-cut materials have also been considered [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the material used (AISI 1020) is a soft steel and does not influence wheel wear. Reliable results using this method were obtained in [19][20][21][22].…”
Section: Methodsmentioning
confidence: 87%
“…With this configuration, surface roughness, roundness deviation, and wheel wear presented lower values than those obtained for grinding with conventional flood cooling. Bianchi et al [20] carried out experiments with the application of the same technique, but with an aluminum oxide grinding wheel. The obtained results also demonstrated that the application of MQL combined with a cleaning jet corresponds to a viable alternative to the use of conventional flood cooling.…”
Section: Introductionmentioning
confidence: 99%